DIGITALISASI NILAI-NILAI ISLAM : ANALISIS KARAKTERISTIK ISLAM DALAM ERA TRANSFORMASI TEKNOLOGI - Chusnul Chotimah (Universitas Muhammadiyah Metro, 2026)
The advancement of technology in the Society 5.0 era has significantly transformed patterns of interaction and religious learning, including the process of internalizing Islamic values. This study aims to analyze the relevance of Islamic characteristics within technological transformation and how digitalization becomes a new medium for strengthening Islamic identity. The research uses a literature review approach by examining journals, books, and scientific publications from the last five years. The findings show that digitalization expands access to Islamic references, enhances digital-based learning, and enables more flexible, inclusive, and adaptive religious engagement. However, ethical challenges arise, such as misinformation, viral culture, and digital hedonism, thus requiring digital literacy and moral filtering based on Islamic principles. The study concludes that digitalization can serve as a constructive space for strengthening Islamic values when used critically and responsibly, making technology not only an information tool but also a medium for moral development and identity formation in modern society. Keywords: digitalisasi, internalisasi, literasi digital